Pollution by Polycyclic Aromatic Hydrocarbons in Sediments and Marine Species: Review - Espinosa Rios, Kellys Johana; Morales Valdelamar, Miguel Angel; Jaramillo-Colorado, Beatriz Eugenia (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Marine sediments are insoluble particles that reach the sea through rivers, they originate from sources such as mineral salts, small rocks, as well as all the remains of animals and organisms that adhere to it when they die. These sediments are being negatively affected by contamination and the presence of polycyclic aromatic hydrocarbons (PAHs), which generates a harmful impact on the flora and fauna of aquatic ecosystems, due to pyrogenic and petrogenic sources, among which industrial operations stand out. and the use of oil, the purpose of this review was to know the main sources of pollution and the concentrations of PAHs in the Colombian coasts, compare them with the rest of America and determine if they complied with the regulations established by the National Oceanic and Atmospheric Administration (NOAA); the effects on marine life were also an important part of this review, due to the damage that PAHs cause to human health.